Built environment and public bike usage for metro access: A comparison of neighborhoods in Beijing, Taipei, and Tokyo. (August 2018) - Lin, Jen-Jia; Zhao, Pengjun; Takada, Kazuyuki; Li, Shengxiao; Yai, Tetsuo; Chen, Chi-Hao
Highlights: Built environments contribute to efforts to explain public bike usage. Empirical knowledge on associations of built environment with public bike usage is not transferable among cities. Collecting local empirical knowledge on travel behavior is critical for developing bike-friendly built environments. Abstract: This article presents a transnational comparison study to clarify the difference in the associations of built environment with public bike usage in three cities in eastern Asia. This study sampled passengers entering or leaving metro stations in seven neighborhoods in Beijing, Taipei, and Tokyo for home-based work trips. Their mode choices of connecting travels between trip origins/destinations and metro stations were analyzed using logit and latent class models. Empirical evidence reveals that the associations of built environments with public bike usage of the study cities rarely accord with one other. Results are unable to support that empirical knowledge on the association of built environment with public bike usage is transferable among transnational cities despite their geographical and cultural proximity. Collecting local empirical knowledge on travel behavior is critical for developing bike-friendly built environments for a city.